Social implications of low-cost rehousing in Kuala Lumpur / Wong Yok Ying - Wong, Yok Ying (1976)
This academic exercise is an attempt to study the social implications of low-cost rehousing in the Federal Territory of Kuala Lumpur. For this purpose, a total of 40 household, then Malay and the Chinese household from each of Jalan loke Yew Phase IV Jalan Cheras Phase IIA Flats were studied. The lives of the household in their former squatter areas and in the flats were compared in terms of structural material and design, expenditure, crowding, health, security, distance to major activity areas and children’s educational performance. In addition, friendship and neighbourhood patterns, racial attitudes and the advantages and disadvantages of living in low-cot flats were covered. The first chapter touches on the background of the study and review of literature. In the second chapter, the author explains the criteria for the selection of flats, households and respondents, the questionnaire, the problems of the interview and the limitations of the study as a whole. The results are presented and discussed in the third chapter. Conclusions and suggestions for the solution of various problems are presented in the fourth and final chapter.